1997
DOI: 10.1177/107110079701801103
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and CT Evaluation of Tibiofibular Syndesmotic Diastasis: A Cadaver Study

Abstract: Twelve cadaver lower limbs were used for radiographic and CT assessment of the tibiofibular syndesmosis. Plastic spacers were placed in the distal tibiofibular intervals of each specimen in successive 1-mm increments until diastasis could be appreciated on the plain radiographs. All 2- and 3-mm diastases could be noted and clearly identified on CT scans, while the 1-, 2-mm, and half of the 3-mm syndesmotic diastases could not be appreciated with routine radiographs. CT scanning is more sensitive than radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(157 citation statements)
references
References 23 publications
6
137
1
13
Order By: Relevance
“…First, we evaluated the syndesmosis reduction only with radiographs. Several studies suggest radiographic evaluations are insensitive when evaluating the syndesmosis [3,7,27]. Gardner et al reported a 52% malreduction seen on CT as compared with apparently well-reduced fractures on plain radiographs [11].…”
Section: Discussionmentioning
confidence: 99%
“…First, we evaluated the syndesmosis reduction only with radiographs. Several studies suggest radiographic evaluations are insensitive when evaluating the syndesmosis [3,7,27]. Gardner et al reported a 52% malreduction seen on CT as compared with apparently well-reduced fractures on plain radiographs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the deltoid ligament can be associated with syndesmotic sprain as they share similar external rotation and eversion mechanisms of injury [ 108 ]. Increased swelling, pain with palpation, ecchymosis over the medial ankle, and greater than 4 mm widening of the syndesmosis on plain fi lms may be indicative of deltoid ligament involvement [ 110 ]. Special clinical tests used for diagnosis of syndesmotic injury include the external rotation test, the squeeze test, the crossedleg test, the cotton test, the point test, the dorsifl exion maneuver, and one-legged hop test [ 108 ].…”
Section: Syndesmosis Instabilitymentioning
confidence: 98%
“…14,15,38,48,58 Ebraheim et al 14,15 have demonstrated that a CT scan is a more accurate and sensitive method for detecting syndesmotic injuries when compared to plain film radiography. A CT scan is particularly sensitive for minor or partial ruptures and to assess diastasis.…”
Section: Imaging Studiesmentioning
confidence: 99%